2010
DOI: 10.4103/0970-0218.66869
|View full text |Cite
|
Sign up to set email alerts
|

A study of gender differentials in the prevalence of tuberculosis based on NFHS-2 and NFHS-3 data

Abstract: Background:Worldwide, the case notification rate of tuberculosis has been reported to be higher for men than women. In India also, the prevalence of TB is higher among males as compared to females but it is important to study the trend of gender gap in the prevalence of tuberculosis over the years.Objective:To examine the trend in gender gap in the prevalence of TB over the years.Materials and Methods:The unit level data of NFHS-2 (1998-99) and NFHS-3 (2005-06) has been utilized. Gender gap in the prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…identified that the gender gap in the prevalence of TB has widened which they attributed to higher underreporting due to social stigma and lack of health seeking behavior. ( 9 ) Our study supports their finding; however, we also found that even when women exhibited health seeking behavior they received delayed care because of their lack of knowledge regarding TB and lack of awareness in free government services. Concurrent with previous studies, many patients first sought care from private practices, most of which have no access to TB training programs.…”
Section: Discussionsupporting
confidence: 88%
“…identified that the gender gap in the prevalence of TB has widened which they attributed to higher underreporting due to social stigma and lack of health seeking behavior. ( 9 ) Our study supports their finding; however, we also found that even when women exhibited health seeking behavior they received delayed care because of their lack of knowledge regarding TB and lack of awareness in free government services. Concurrent with previous studies, many patients first sought care from private practices, most of which have no access to TB training programs.…”
Section: Discussionsupporting
confidence: 88%
“…From the total calculation, 88% of respondents lived in rural areas while the other 12% lived in urban areas. 46 Differences in findings could be due to the imbalanced number of male and female respondents and other characteristics in this study. This study involved nurses as the highest number of respondents compared to other healthcare professions (42.05%).…”
Section: Discussionmentioning
confidence: 72%
“…Contrarily, a population-based study in the Hamar of Ethiopia indicated that hydatid disease was a public health problem for women [54]. Irrefutably, gender differentials also exist in the prevalence of TB [55]. …”
Section: Discussionmentioning
confidence: 99%